Pengaruh Prāṇāyāma Terhadap Peningkatan Kapasitas Vital Paru Pada Remaja Di Santi Srama Bulaki Studio Yoga - Putri Ramuja Dewi Sugata; I Made Sugata; Putu Emy Suryanti (UHN IGB Sugriwa Denpasar, 2023)
A lifestyle that tends to be positive and healthy will have a better quality. One of the organs of the body that is very influential when a person's lifestyle is unhealthy is the part of a person's lungs. The lung organ has an ability that is supported by two factors in it, namely the volume of oxygen that will enter the body and of course another one in the vital capacity of the lungs to accommodate this oxygen. One of the factors that can influence the increase in lung vital capacity is prāṇāyāma practice. Prāṇāyāma is a regulation of good breath in and out of the lungs through the nostrils with the aim of spreading Prana (energy) to all parts of the body and increasing the vital capacity of the lungs. This prāṇāyāma practice technique can be practiced at Santi Srama Bulaki Yoga Studio. The research method used is quantitative with a research design